Sleep and COVID-19: considerations about immunity, pathophysiology, and treatment - Mello, Marco Túlio De; Silva, Andressa; Guerreiro, Renato de Carvalho; da-Silva, Flavia Rodrigues; Esteves, Andrea Maculano; Poyares, Dalva; Piovezan, Ronaldo; Treptow, Erika; Starling, Marcelo; Rosa, Daniela Santoro; Pires, Gabriel Natan; Andersen, Monica Levy; Tufik, Sergio (Sleep Science, 2020)
The fear and uncertainty caused by the coronavirus disease 2019 (COVID-19) pandemic, threats to survival are one of the main problems of everyday life; however, mental health care must also be considered a priority. During social isolation also called self-quarantine, the restricted mobility and social contact, concern about financial resources and availability of supplies, fear of infection, questions about the duration of self-quarantine, cause anxiety, depression, stress, insomnia and reduced the quality and quantity of sleep, that may present a greater risk to the health of the general population. Sleep disorders are increasingly becoming a major health issue in modern society, and are influenced by retinal stimulation by electronic devices, as well extended and/or night shift-work, which may aggravate the systemic and lung inflammation during viral infections. Sleep disorders can induce pro-inflammatory states and be harmful during the COVID-19 pandemic. The possible interactions between many drugs used to treat COVID-19, and those used to treat sleep disorders are unknown, mostly due to the lack of a standard protocol to treat these patients. Insufficient sleep or irregular sleep-wake cycles may impair health, immune system, induce pro-inflammation state, and may lead to increased vulnerability to viral infections, involving inflammatory and oxidative/antioxidant imbalance. In this sense, obstructive sleep apnea has been associated with recognized COVID-19 risk comorbidities and considered a risk factor for COVID-19. During the COVID-19 pandemic, health care cannot stop, and telemedicine has presented itself as an alternative method of delivering services. When a face-to-face visit is mandatory, or in locations with minimal community transmission where sleep centers have resumed activities, it is important that the sleep center facilities are properly prepared to receive the patients during the COVID-19 pandemic, and follow all relevant safety rules. In this work we gathered a group of researchers, specialists in aspects related to chronobiology, sleep, sleep disorders, and the immune system. Thus, we conducted a narrative review in order to address the relationship between COVID-19 and sleep, as well as its immunological aspects and strategies that may be applied in order to mitigate the harmful effects on health that affects everyone during the pandemic.
Keywords: Sleep; Sleep Wake Disorders; SARS Virus; Coronavirus Infections; Immune System; Therapeutics